Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Menjadi Akuntan - Nabila, Alika Fiqria; Dethan, Minarni Anaci; Muga, Maria Prudensiana Leda (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2025)
This study aims to determine the influence of the work environment, financial rewards, personalities, and educational expenses on students' interest in a career as an accountant. Research has found that work environment, financial rewards and personalities have a positive effect on students’ interest in a career as an accountant. However, the result of previous research has been somewhat inconsistent because of different results. The subjects of this study were accounting students from Universities in Kupang City. This study uses a quantitative approach by distributing questionnaires through google form. The sample of this study was 100 respondents. Data analysis carried out is descriptive statistical analysis, data quality test multiple linear analysis and hypothesis testing using the IBM SPSS 26. The results of this study show that work environment, financial rewards, and educational expenses have a partial effect on students' interest in selecting a career as an accountant, while personalities do not affect students' interest in an accountant career. Other results show that work environment, financial rewards, personalities, and educational expenses simultaneously affect the students' interest in an accountant career with a determination coefficient value of 38.3%.